Retrospective Review of Transpulmonary Pressure Guided Positive End-Expiratory Pressure Titration for Mechanical Ventilation in Class II and III Obesity. (29th April 2022) - Liou, Jesse; Doherty, Daniel; Gillin, Tom; Emberger, John; Yi, Yeonjoo; Cardenas, Luis; Benninghoff, Michael; Vest, Michael; Deitchman, Andrew
Abstract : OBJECTIVES: Acute respiratory distress syndrome is treated by utilizing a lung protective ventilation strategy. Obesity presents with additional physiologic considerations, and optimizing ventilator settings may be limited with traditional means. Transpulmonary pressure (PL ) obtained via esophageal manometry may be more beneficial to titrating positive end-expiratory pressure (PEEP) in this population. We sought to determine the feasibility and impact of implementation of a protocol for use of esophageal balloon to set PEEP in obese patients in a community ICU. DESIGN: Retrospective cohort study of obese (body mass index [BMI] ≥ 35 kg/m 2 ) patients undergoing individualized PEEP titration with esophageal manometry. Data were extracted from electronic health record, and Wilcoxon signed rank test was performed to determine whether there were differences in the ventilatory parameters over time. SETTING: Intensive care unit in a community based hospital system in Newark, Delaware. PATIENTS: Twenty-nine mechanically ventilated adult patients with a median BMI of 45.8 kg/m 2 with acute respiratory distress syndrome (ARDS). INTERVENTION: Individualized titration of PEEP via esophageal catheter obtained transpulmonary pressures. MEASUREMENTS AND MAIN RESULTS: Outcomes measured include PEEP, oxygenation, and driving pressure (DP) before and after esophageal manometry at 4 and 24 hr. Clinical outcomes including adverse events (pneumothorax and pneumomediastinum), increased vasopressor use, rescue therapies (inhaled pulmonary vasodilators, extracorporeal membrane oxygenation, and new prone position), continuous renal replacement therapy, and tracheostomy were also analyzed. Four hours after PEEP titration, median PEEP increased from 12 to 20 cm H2 O ( p < 0.0001) with a corresponding decrease in median DP from 15 to 13 cm H2 O ( p = 0.002). Subsequently, oxygenation improved as median Fio 2 decreased from 0.8 to 0.6 ( p < 0.0001), and median oxygen saturation/Fio 2 (S/F) ratio improved from 120 to 165 ( p < 0.0001). One patient developed pneumomediastinum. No pneumothoraces were identified. Improvements in oxygenation continued to be seen at 24 hr, compared with the prior 4 hr mark, Fio 2 (0.6–0.45; p < 0.004), and S/F ratio (165–211.11; p < 0.001). Seven patients required an increase in vasopressor support after 4 hours. Norepinephrine and epinephrine were increased by 0.05 (± 0.04) µg/kg/min and 0.02 (± 0.01) µg/kg/min on average, respectively. CONCLUSIONS: PL -guided PEEP titration in obese patients can be used to safely titrate PEEP and decrease DP, resulting in improved oxygenation.